A cost and community perspective on the barriers to microbiome data reuse - Julia M. Kelliher; Julia M. Kelliher; Leah Y. D. Johnson; Francisca E. Rodriguez; Jaclyn K. Saunders; Marie E. Kroeger; Buck Hanson; Aaron J. Robinson; Winston E. Anthony; Marc W. Van Goethem; Anders Kiledal; Ahmed A. Shibl; et al. (Frontiers in Bioinformatics)
Microbiome research is becoming a mature field with a wealth of data amassed from diverse ecosystems, yet the ability to fully leverage multi-omics data for reuse remains challenging. To provide a view into researchers’ behavior and attitudes towards data reuse, we surveyed over 700 microbiome researchers to evaluate data sharing and reuse challenges. We found that many researchers are impeded by difficulties with metadata records, challenges with processing and bioinformatics, and problems with data repository submissions. We also explored the cost constraints of data reuse at each step of the data reuse process to better understand “pain points” and to provide a more quantitative perspective from sixteen active researchers. The bioinformatics and data processing step was estimated to be the most time consuming, which aligns with some of the most frequently reported challenges from the community survey. From these two approaches, we present evidence-based recommendations for how to address data sharing and reuse challenges with concrete actions for future work.